Efektivitas Penarapan Aplikas Karejo di Dinas Lingkungan Hidup Sumatra Utara khususnya di bidang Pengendalian Pencemaran Kerusakan Lingkungan (PPKL). - Nadhrah al aflah; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
TAM is a way to understand how external factors can influence what we think, feel and want. The TAM approach is designed to help people embrace new technologies by focusing on several key factors. The TAM theory provides a theoretical basis for how these factors interact. With this TAM theory approach. Users can first understand and learn how to use the application, for example the karejo application which has just been used and there are still many employees from the North Sumatra Environmental Service who do not really understand how the application works. This is influenced by the fact that in today's digital era, many applications are needed as tools to carry out various activities. One of the applications is the karejo application which is used by the North Sumatra Environmental Service as a means to facilitate various activities both in terms of work supervision, reporting of performance results, employee absences and various other activities.